Function of Human Resources Manager in Making Employee Employment Contracts and Employee Development - Devi Marlita (Dinasti International Journal of Economics, Finance & Accounting, 2024)
Abstract: The article on the function of human resource managers in making employee employment contracts and employee development is a scientific literature review article within the scope of human resource management science. The purpose of this writing is to build a hypothesis of the influence between variables which can later be used for further research within the scope of human resource management. The research method used is descriptive qualitative. Data was obtained from previous research that is relevant to this research and sourced from academic online media such as Publish or Perish, Google Scholar, digital reference books and Sinta journals. The results of this article are: 1) Human resources managers play a role in creating employee work contracts; 2) The human resources manager plays a role in meeting the needs of the company and employees in making employee work contracts; and 3) Human resources managers play a role in employee development. Keyword: Human Resources Manager, Making an Employee Employment, Employee Development